Xúc tác quang micro nanocompozit trên cơ sở TiO2 – nanocacbon mang trên vật liệu đệm cacbon có cấu trúc - Anh và cộng sự, Ngô Tuấn (Vietnam Journal of Chemistry, 2014)
Composite TiO2/Carbon nano based photocatalysts are being investigated abundantly in the world because of their high photoactivity and their capacity in absorbing almost of suns irradiation. By absorbing a photon, these catalysts can promote the total oxidation of organic compounds to CO2, H2O products. However, researches about this composite are just for a the powder catalysts applications in a batch reactor. Their uses in the continuous system seem impossible. In Vietnam, these catalysts are completely untouched. Therefore, our researches are now focused onto the new photocatalysts based on composite TiO2 commercial, sol-gel/carbon nano with macroscopic shaping. This new type of catalyst allows amplifying the photoactivity and reducing the cost. These catalysts were successfully applied in our laboratory for continuous systems to degradate organic compounds in waste water.